The Feminine Sacred: An Ontosociology of Woman as a Symbol - Jacinto Choza (Religions)
In contemporary development, feminism is divided into two major trends, that of difference and that of equality. The former tends to rely more on ontology and religious symbolism, and the latter on sociology and political praxis. This paper aims to show that this antagonism has as its background the complementarity and unity between both approaches, which are based on religious symbolism. Religious symbolism has both an ontological value and a sociological value, which give both internal consistency and external form to society.